The Balkan cultures: dialogue, transfer, metamorphoses (Colloquia Comparativa Litterarum, 2025)
The Balkan Cultures: Dialogue, Transfer, Metamorphoses. Ed. Orlin Sabev, Lora Taseva, Antoaneta Belcheva. Sofia, IBSCT – BAS, 2023.